Learning Logic Gate through 7-Gates - Hanasrullah Halim; Wan Amirah Najwa Wan Idris; Haslina Hassan; Ismail Yusuf Panessai (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
This game is a simple method for a student that try to learn in Logic Gates, an educational game with futuristic adventure. The only way for the player to save the digital world in this game by using Logic Gates, with Logic Gates formulas the player can make the power connection on the circuit to the digital world engine. Without knowing how Logic Gates functional will make the player losing the power for the engine to the digital world. 7 Gates Digital World is a complex genre game. The main genre for this game absolutely is an Educational Game. Although, the game developer made a complex genre for this educational game. Puzzle include in this game combined with platforms games style the player must collect all the switches in confusion platform map to go through the next portal to the next level. Educational genre in this game giving the content level completely based on the level of understanding and give the player to memorize every gates formula.